Times of the Self in Kingston, Jamaica†. Issue 3 (27th May 2017) - Wardle, Huon
ABSTRACT: Revival Zionists – a small spiritist following in Jamaica – describe how their relations with spirits allow them to bring personal spiritual gifts to bear on every day or 'temporal' experience. Taking a hint from Kant that 'time itself does not change but only something which is in time', the article considers the timely logic of these 'gifts'. In a social-economic situation characterised by paucity of material resources but plenitude of labour-time, spiritual gifts reappear as a valued ground for a person's reputation. Likewise, we may also see them as one example of an attempt to organise the relationship between homo noumenon and homo temporalis .